An investigation into Iranian English learners’ use of cognitive strategies and writing performance across different language backgrounds and proficiency levels - Fatemeh Poorebrahim (Research and Development in Medical Education, 2020)
Background: The significance of strategy use in writing is well established. However, particular strategy types which different learners can use in different contexts provides invaluable insights for the stakeholders. The current study examined the frequency of cognitive strategy use in writing as well as the quality of writing produced by language learners at different levels of proficiency (high or low) and from different language backgrounds (Turkish-Persian or Persian). Methods: For this study, 176 Iranian learners of English were divided into bilingual (n=91) and monolingual (n=85) categories and participants were placed at high (n=95) or low (n=81) proficiency levels based on their scores on the Test of English as a Foreign Language (TOEFL) administered for placement purposes. The research data was collected through writing cognitive strategy questionnaire and argumentative writing samples. Results: The results of ANOVA and Mann-Whitney tests revealed that (1) language background and proficiency level could jointly affect the frequency of cognitive strategy use, (2) could each influence the quality of the written products on its own, and (3) the strongest relationship between cognitive strategy use and writing quality existed among the bilingual participants with high language proficiency. Conclusion: Knowing a second language may increase learners’ use of writing cognitive strategies, thereby enhancing the quality of their writing. These findings could prove useful for English as a Foreign Language (EFL) teachers and content developers.